Plant-parasitic nematode research in the arid desert landscape: a systematic review of challenges and bridging interventions - Elhady, Ahmed; Alghanmi, Linah; Abd-Elgawad, Mahfouz M. M.; Heuer, Holger; Saad, Maged M.; Hirt, Heribert (Frontiers in Plant Science, 2024)
Plant-parasitic nematode research in the Middle East and North Africa (MENA) faces significant challenges rooted in a need for proper assembly, diversity, and a unified and purpose-driven framework. This led to exacerbating their detrimental effects on crop production. This systematic review addresses the current situation and challenges that require targeted interventions to sustainably manage plant-parasitic nematodes and reduce their detrimental impact on agriculture production in the MENA region. We analyzed the nematode-related research conducted within the region over the past three decades to assess available resources and promote diverse research approaches beyond basic morphology-focused surveys. We show that crops are attacked by a diverse spectrum of Plant-parasitic nematodes that exceed the global economic threshold limits. In particular, Meloidogyne species exceed the threshold limit by 8 -14-fold, with a 100% frequency of occurrence in the collected soil samples, posing a catastrophic threat to crop production and the economy. We highlight detrimental agriculture practices in the MENA region, such as transferring soil from established fields to barren land, which enhances the dissemination of plant-parasitic nematodes, disrupting soil ecology and causing significant agricultural challenges in newly cultivated areas. Looking into the behavior of farmers, raising awareness must be accompanied by available solutions, as more practical alternatives are needed to gain the confidence of the farmers. We propose integrating microbial-based products and soil development practices in hygienic farming as resilient and sustainable solutions for nematode management. Increased emphasis is required to diversify the nematode-related research areas to bridge the gaps and facilitate the transition from fundamental knowledge to practical solutions. A cohesive network of nematologists and collaboration with national and international entities is crucial for exchanging knowledge related to legislation against invasive species.